Implementation of Advanced Technology in Waqf Management: A Systematic Literature Review - Maretaniandini, Sessa Tiara; Hilmiyah, Fadilatul; Akbar, Syahrir; Adam Hamid, Abdelsalam (Universitas Muhammadiyah Surakarta, 2025)
This systematic literature review explores the implementation of advanced technology in waqf management by mapping and classifying key research themes and trends. Utilizing the PRISMA protocol, an initial search across Scopus, OpenAlex, Crossref, and Google Scholar identified 1,289 articles. These were then screened for relevance based on inclusion and exclusion criteria, resulting in 17 articles selected for in-depth analysis. The thematic mapping reveals four dominant clusters: (1) blockchain technology, which is frequently discussed for its potential to enhance transparency and accountability in waqf transactions; (2) cash waqf and digital waqf, highlighting innovations in fundraising and asset management; (3) artificial intelligence and fintech, which are explored for improving risk assessment, fund allocation, and operational efficiency; and (4) digital platforms, which are recognized for expanding accessibility, facilitating public participation, and streamlining waqf processes. The review also identifies significant challenges, including regulatory gaps, limited technological infrastructure, and stakeholder resistance to change. At the same time, best practices from countries such as Malaysia, Singapore, and Oman illustrate successful technology adoption in waqf management. By systematically mapping these themes, this study provides a comprehensive overview of the research landscape, offers practical insights for policymakers and practitioners, and highlights the need for further empirical research to measure the real-world impact of technology implementation in diverse waqf contexts.